Religion and urban political eco/pathology: exploring communalized coronavirus in South Asia. Issue 2 (4th May 2021) - Mehmood, Asif; Hasnain, Sajjad; Azam, Muhammad
ABSTRACT : wWe use the urban political ecology perspective to explore how communities of homo religiosus (re)configure politics of COVID-19 in India and Pakistan. This urban health crisis unfolds in five parallel registers of conflictualities: (i) where religious communities carve out a domain for self-governance of the pandemic with their own 'knowledge and truths', (ii) where embodied religious practices challenge or undermine state biopower and transform governmentalities, (iii) where the spatial dimension of conflict evolves into the crisis of technologies of governance, (iv) where religious identities are stigmatized and the minority groups are excluded and (v) where communalism organizes around international relations. It is argued that religious groups in South Asia influenced the urban political (eco)pathology with their disruptive potential which transformed biosecurity regimes and enhanced health risks on the one hand and on the other, they embraced and internalized discords of disease within their antagonistic communal and sectarian memories and histories and weaponized the pandemic to produce more cracks in the social fabric. This essay underscores the significance of unusual actors in the urban political ecology framework and calls for a renewed understanding of human–nature interface by incorporating religion and religious beliefs and how they view and shape the metabolic flows in the urban spaces for social sustainability of the city as a 'natural object'.